Faktor Perencanaan Suksesi Generasi Pertama Berbasis Family Business Enterprise (Studi Kasus pada Toko Emas di Kota Bandung) - Raphaela Medisa; Syahputra Syahputra (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
In the city of Bandung, there are many businesses established by the family of one of them a gold shop. Gold entrepreneurs managed to get bright prospects by choosing the next generation who came from family members. However, researchers must find the truth about this research. The purpose of this study is to study the factors that influence the first generation in selecting the next generation with succession planning in the family business to survive for a long time. The 24 variables in the first generation succession planning research in the family business support six theories, Alcorn (1982), John Ward (1998), Alan Carsrud (2006), Soedibyo (2007), Boyd, Royer, Pie, and Zhang (2015) and Ghee, Ibrahim and Halim (2015). This research is a quantitative factor analysis study. The population is known to researchers through surveys to gold shops in Bandung, amounting to 120 populations and 60 respondents. Data were then processed by a factor analysis method through the help of SPSS version 23 for Windows. The research produced five factors that enhance the success of the first generation of planning to choose the next generation in the gold shop family business in the city of Bandung. The five factors are competent next generation factors of 30,014%, the main focus of the target factor is 11,157%, the business relationship factor with the family is 11,081%, the first generation factor is 11,044% and the planning and succession control factor is 10,642%. The total to 73,938%, so there was another factor of 26.02% which affected the generation of information for family businesses in Bandung. Keywords: First generation, decision making, succession planning